Influence of Incresment Kappaphycus alvarezi Porridge Toward Elops hawaiensis Meatballs Characteristic - Siti Amaliah; Aris Munandar; Sakinah Haryati (Jurnal Perikanan dan Kelautan, 2016)
Hawaiian Ladyfish (Elops hawaiensis) can be used as raw material for fish gel (jellyfish product) due to its white fleshy and high protein. One of the diversified fisheryproducts are fish meatballs. This product is an effort to diversify from ladyfish forincrease domestic fish consumption. The addition of seaweed porridge Kappaphycusalvarezii mush on fish meatballs ladyfish expected to improve the quality ofmeatballs. The aim of this study was to determine the characteristics of fish ballshawaiian ladyfish (Elops hawaiensis) with the addition of seaweed porridgeKappaphycus alvarezii and find out the nutritional value of Hawaiian ladyfishmeatballs. Addition seaweed porridge concentration used in making meatballs is 0%,5%, 10%, 15%, and 20%. The experimental design used was a completelyrandomized design with two replications. Data were analyzed by analysis of variance(ANOVA) and Duncan test further. Fish meatballs with the addition of a slurry ofseaweed porridge Kappaphycus alvarezii 10% is the best fish balls with organolepticcharacteristics sighting value (6.58), texture (6.47), flavor (6.22), color (6.33), aroma(6.02); and the value of physical characteristics such as folding test (4.83), bite test(7.26), gel strength (802.55 gf.cm); and chemical characteristics such asmoisture content (68.60% w/w), ash content (1.39% w/w), protein content (12.42%w/w), fat (1,10% w/w), and levels of dietary fiber (4,98% w/w).